Porphyrinic Metal–Organic Framework Quantum Dots for Stable n–i–p Perovskite Solar Cells. (16th November 2022) - Liu, Yinjiang; Liu, Tao; Guo, Xi; Hou, Meichen; Yuan, Yihui; Shi, Se; Wang, Hui; Zhang, Rui‐Zhi; Galiotis, Costas; Wang, Ning
Abstract: As the power‐conversion efficiency (PCE) of organic–inorganic lead halide perovskite solar cells (PSCs) is approaching the theoretical maximum, the most crucial issue concerns long‐term ambient stability. Here, the application of PCN‐224 quantum dots (QDs) is reported, a typical Zr‐based porphyrinic metal–organic framework (MOF), to enhance the ambient stability of PSCs. PCN‐224 QDs with abundant Lewis‐base groups (e.g., CO, C−N, CN) contribute to high‐quality perovskite films with enlarged grain size and reduced defect density by interaction with under‐coordinated Pb 2+ . Meanwhile, PCN‐224 QDs enable the well‐matched energy level at the perovskite/hole transport layer (HTL) interface, thereby facilitating hole extraction and transport. More importantly, PCN‐224 QDs‐treated HTL can capture Li + from bis(trifluoromethanesulfonyl)imide additive, leading to the reduced aggregation and less direct contact with moisture for hygroscopic Li‐TFSI. Moreover, PCN‐224 QDs mitigated Li + ion migration into the perovskite layer, thus avoiding the formation of deleterious defects. The resultant devices yield a champion PCE of 22.51%, along with substantially improved durability, including humidity, thermal and light soaking stabilities. The findings provide a new approach toward efficient and stable PSCs by applying MOF QDs. Abstract : PCN‐224 quantum dots (QDs) with abundant Lewis base groups are incorporated into perovskite layer and hole transport layer (HTL) of perovskite solar cells (PSCs). PCN‐224 QDs enable strong coordination interaction with the under‐coordinated Pb 2+ ions in perovskite film and mobile Li + ions in HTL, ultimately leading to superior humidity, thermal, light stress, and operational stabilities of PSCs.